Some Contributions of Economics to the Study of Personality - James J. Heckman; Tomás Jagelka; Tim Kautz (Institute of Labor Economics (IZA), 2019)
This paper synthesizes recent research in economics and psychology on the measurement and empirical importance of personality skills and preferences. They predict and cause important life outcomes such as wages, health, and longevity. Skills develop over the life cycle and can be enhanced by education, parenting, and environmental influences to different degrees at different ages. Economic analysis clarifies psychological studies by establishing that personality is measured by performance on tasks which depends on incentives and multiple skills. Identification of any single skill therefore requires isolation of confounding factors, accounting for measurement error using rich data and application of appropriate statistical techniques. Skills can be inferred not only by questionnaires and experiments but also from observed behavior. Economists advance the analysis of human differences by providing anchored measures of economic preferences and studying their links to personality and cognitive skills. Connecting the research from the two disciplines promotes understanding of the number and nature of skills and preferences required to characterize essential differences.
Keywords: D91; D12; C93; C91; D9; 330; preferences; psychology; behavioral economics; human diversity